The impact of audit findings and follow-up actions on audit recommendations on audit opinions of financial statements with APIP capabilities as a moderating variable (A study on provincial/regencies/cities governments in Suluttenggo Region) - Indriani, Dwinta; Tinangon, Jantje J.; Budiarso, Novi S. (The Contrarian : Finance, Accounting, and Business Research, 2024)
The audit opinion issued on government financial statements is the conclusion of the BPK audit process. These opinions provide a qualitative picture of financial management, reflecting the accountability and transparency of local government. This research analyses the influence of audit findings and follow-up actions on audit recommendations (or TLRHP) on audit opinions and examines the moderating effect of APIP capabilities on this relationship. An analytical method employed is binary logistic regression analysis with the absolute difference test. This study used secondary data from the BPK IHPS and the Financial and Development Supervisory Agency (or BPKP) annual performance report. The data encompasses 37 provincial, regency, and city governments in North Sulawesi, Central Sulawesi, and Gorontalo for the fiscal period 2018 to 2022. The results reveal that audit findings have no significant impact on audit opinions. Conversely, both TLRHP and APIP capabilities have a significant influence on audit opinions. Furthermore, APIP capabilities moderate the relationship between TLRHP and audit opinions but not the relationship between audit findings and opinions.